Is damage to the pre-frontal cortex dormant until adolescence, or difficult to detect? Looking for keys that unlock executive functions in children in the wrong place. (October 2017) - Tonks, James; Williams, W. Huw; Slater, Alan; Frampton, Ian
Abstract: A range of functions can be negatively affected by pre-frontal cortex (PFC) injury, but observed behavioural and social changes are commonly linked to post-injury changes in executive function. Executive functioning is a complex neuropsychological construct which is further complicated by neuro-developmental processes when applied to children. There is a substantial and continuing evidence base that supports the view that early childhood pre-frontal cortex (PFC) injury results in hidden, dormant, or sleeping effects. In contrast, recent and rapidly accruing contemporary studies provide preliminary evidence that challenge the view that PFC associated impairments are completely 'hidden'. Studies that examine the various functions of the PFC and differentiate these to provide preliminary evidence to indicate earlier EF development than that which develops upon reaching adolescence, are reviewed here, together with research that identifies early predictors of later EF impairments. It remains that studies of PFC function and/or structural brain-changes are substantially complicated by issues related to definition regarding functions of the PFC, measurement of EF and other PFC-related functions that may be better understood as meta-processes. These issues are discussed in the concluding sections of this paper.